Strategies for strengthening cervical cancer screening programmes in Gwanda district, Zimbabwe: a qualitative study - Fennie Mantula; Yoesrie Toefy; Vikash Sewram (BMC Public Health)
Abstract Background Numerous studies have been conducted on barriers to cervical cancer screening in low resourced settings. Few have however explored the factors that motivate women to make the decision for screening. This study therefore aimed at identifying strategies that could strengthen the utilisation of screening services, with the goal of informing the development of context for enhancing cervical cancer programmes in Gwanda district, Zimbabwe. The socio-ecological model that implies individual, inter-personal, community, and health system factors as influencers of screening behaviours guided the study. Methods A cross sectional qualitative design using five focus group discussions with 36 screening-eligible women aged 25–50 years, and 25 in-depth interviews of health providers with varied responsibilities in the screening programme were conducted. Data were analysed thematically with the aid of the Web Atlas.ti software. Results Key findings suggest that women’s willingness to be screened, on-going awareness campaigns and an increasing number of screening sites and nurses trained in screening procedures promote the uptake of screening. Concomitantly, awareness and knowledge about cervical cancer screening, male support, and community involvement in planning and implementation of programmes were seen as facilitators to screening, with accessibility of cervical cancer screening services being recognised as the most important. Conclusions To exploit on women’s willingness to be screened, delivery of screening services need to be re-engineered through development of strategies for increased and sustained educational programmes and increase of screening facilities. This could effectively address the prevalent barriers and enhance the facilitators for screening uptake.